Psychological stress, depression and social skills of military police (Research, Society and Development, 2020)
Social skills are often correlated with mental health índex. The present study aimed to verify correlations between stress, depression and social skills of military police officers. The study was conducted by 129 police officers (93% men), with a mean age of 29.71 years (Standard Deviation=4.88) who answered a sociodemographic form, Perceived Stress Scale – PSS-14, Patient Health Questionnaire-9 – PHQ-9 and Social Skills Inventory – IHS-Del-Prette. The results showed that the most frequent situations of greater stress in military police work were lack of professional recognition and interpersonal relationships, which represented almost half (45.8%) of the answers, leaving in second place the discomforts with the main activities. The comparison between the means of psychological stress and depression by sex revealed statistically significant differences (p